2023
DOI: 10.3390/microorganisms11030761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofilm Cultivation Models for Efficacy Testing of Disinfectants against Salmonella Typhimurium Biofilms

Abstract: Within the European Union, Salmonella is frequently reported in food and feed products. A major route of transmission is upon contact with contaminated surfaces. In nature, bacteria such as Salmonella are often encountered in biofilms, where they are protected against antibiotics and disinfectants. Therefore, the removal and inactivation of biofilms is essential to ensure hygienic conditions. Currently, recommendations for disinfectant usage are based on results of efficacy testing against planktonic bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Moreover, our recently published study demonstrated that disinfectant concentrations, which were evaluated using standardized protocols for the disinfection of cell suspensions (EN 1656), are not high enough to achieve a ≥4 log 10 CFU reduction when tested against biofilms. In this study, on the S. Typhimurium reference strain ATCC 14028, the concentrations of the same disinfectants needed to give a ≥5 log 10 reduction, according to EN 1656, were 0.03% with glutaraldehyde and 0.002% with peracetic acid [24,29]. This shows that there is a necessity for significantly higher concentrations of disinfectants when biofilms are a concern and emphasizes the importance of also testing bacteria in biofilms when evaluating disinfectants on wild-type strains [30].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Moreover, our recently published study demonstrated that disinfectant concentrations, which were evaluated using standardized protocols for the disinfection of cell suspensions (EN 1656), are not high enough to achieve a ≥4 log 10 CFU reduction when tested against biofilms. In this study, on the S. Typhimurium reference strain ATCC 14028, the concentrations of the same disinfectants needed to give a ≥5 log 10 reduction, according to EN 1656, were 0.03% with glutaraldehyde and 0.002% with peracetic acid [24,29]. This shows that there is a necessity for significantly higher concentrations of disinfectants when biofilms are a concern and emphasizes the importance of also testing bacteria in biofilms when evaluating disinfectants on wild-type strains [30].…”
Section: Discussionmentioning
confidence: 73%
“…Both disinfectants were neutralized for at least five minutes. Neutralizer toxicity and disinfectant neutralization validation checks were performed, as described in Richter/Konrat et al 2023 [24]. The method was performed according to Richter/Konrat et al 2023 [24] with some modifications.…”
Section: Biofilm Morphotypingmentioning
confidence: 99%
See 3 more Smart Citations